Profil Darah Monyet Ekor Panjang (Macaca fascicularis) Liar di Habitat Alami - Soma, I Gede; Wandia, I Nengah; Putra, I GA Artha; Silta, Rostiani (Veterinary Science and Medicine Journal; Vol. 1 No. 1 2013, 2013)
Study of blood profile of Macaca fascicularis in wild habitat was conducted using 29 blood samples of  adult Macaca fascicularis from Alas Purwo National Park and Baluran National Park, East Java. Blood samples of Ketamine-anaesthetized Macaca fascicularis were taken via femoral vein. Data were divided according to the sex. The result showed that there was sexual dimorphisms of blood profiles of adult Macaca fascicularis . Blood profiles of the adult male were the total erythrocytes count: 4.9 ± 0.4 (x10 6 /µl), hemoglobin titer: 10.9 ± 0.9 g/dl, packed cell volume: 35.5 ± 3.5%, blood sedimentation rate: 1.5 ± 0.2 mm/h, MCH: 20.9 ± 2.1 pg, MCV: 63.8 ± 5.7 fL, MCHC: 28.7 ± 2.5 pg, total leukocytes count: 5777 ± 551.1/µl, limphocytes 23.6 ± 1.6%, neutrophils 57.2 ± 1.7%, eosinophils 9.6 ± 0.5%, and monocytes 9.6 ± 0.6%. Blood profiles of adult female were the total erythrocyte count: 3.9 ± 0.5 (x10 6 /µl), hemoglobin titer: 8.8 ± 1.7 g/dl, packed cell volume: 32.1 ± 4.1%, blood sedimentation rate: 1.3 ± 0.3 mm/h, MCH: 20.5 ± 4.2 pg, MCV: 74.8 ± 9.9 fl, MCHC: 24.1 ± 4.7 pg, total leukocytes count: 5244.4 ± 1017,9/µl, limphocytes: 22.9 ± 1.8%, neutrophils 56.3 ± 1.7%, eosinophils 11.2 ± 0.7%, and monocytes 9.6 ± 0.6%.
Keywords: Macaca fasciculari; blood profile; wild habitat